Customer loyalty assessment in Malaysian Islamic Banking using Artificial Intelligence - Kishada, Zeyad M. Em.; Mustapha, Aouache; Norailis Ab Wahab (Asian Research Publishing Network, 2024)
Indexed by Scopus